Combating Disinformation in the European Union: Legal Aspects - Zvozdetska, Oksana (Mediaforum : Analytics, Forecasts, Information Management, 2021)
Today, both Ukraine and European countries are subject to disinformation and foreign intervention in their domestic policies. Each democracy no matter its geography experiences its distinct vulnerabilities and respectively, reactions to foreign interference. It should be stated, the immediate responses to such challenges in most Western countries have been rare and sluggish, hampered by legal constraints and bureaucracy, and furthermore, they lacked a real political awareness of the problem or proof of its further impact. Foreign actors are increasingly using disinformation strategies to influence public debate, stir controversy and interfere in democratic decision-making. Responding to these new challenges, the European Commission has introduced a set of actions and tools to better regulate the digital ecosystem of the media and its participants, in particular, the formation and improvement of the legal framework to combat disinformation in the European information space. The researcher’s focus revolves around the European Union’s comprehensive approach to vigorous combating misinformation. The research data prove that since 2015, the EU has adopted a number of regulations to counter this information threat and the potential effects of foreign interference. In particular, in 2016 the EU adopted a document “Joint Framework on countering hybrid threats, a European Union response”, and “Action Plan against Disinformation”, respectively in 2018. These documents provide a baseline for understanding the diverse types of challenges other countries face and how they are addressing them. Consequently, a number of initiatives and projects of the European institutions, and the first worldwide self-regulatory “EU Code of Practice on Disinformation” issued in 2018 on a voluntary basis, have become main pillars of the EU. The Code identifies issues related to ensuring the transparency of political advertising, strengthening efforts to close active counterfeits. accounts, enabling users to report misinformation and access various news sources, while improving the visibility and reliability of authoritative content; enabling the research community to monitor disinformation on the Internet through access to these platforms, compatible with the confidentiality signed by the largest Internet platforms and social media (Google, Facebook, Twitter and Mozilla) in the framework of WMC self-regulation activities. It should be noted that the implementation of the “European Union Code of Practice on Countering Disinformation” has yielded ambiguous fruits. Self-regulation was the first logical and necessary step, but few stakeholders were fully satisfied with the process or its outcome, significant challenges remain for building trust through industry, governments, academia and civil society engagement.